2014
DOI: 10.1007/s10461-014-0821-0
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Anal Sexarche and Co-occurring Sexual Risk are Associated with Current HIV-Related Risk Behaviors Among an Online Sample of Men Who Have Sex with Men in Asia

Abstract: Studies of heterosexual populations across the globe and men who have sex with men (MSM) in a few developed countries showed that earlier sexual debut (sexarche) was associated with higher levels of co-occurring and subsequent HIV risk behaviors. We examined the relationships between earlier anal sexarche, unprotected earlier anal sexarche and current HIV risks among MSM from Asia. A cross-sectional online survey was conducted among MSM (N = 10,826) in Asia in 2010. Bivariate and multivariable logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, these messages may not be effectively saturating communities of younger MSMSW, which may be contributing to high rates of HIV incidence across Asia in populations of very young MSM. 26 While it is encouraging to see that MSMSW in their 20s may be receiving HIV testing, perhaps as a result of exposure to MSM-focused HIV prevention and sexual health information online, 24 this study demonstrates the importance of reaching communities of young MSM, who may be involved in sex work, with salient HIV testing messages. We also found that having other STIs was associated with a higher likelihood of being tested for HIV.…”
Section: Discussionmentioning
confidence: 81%
“…However, these messages may not be effectively saturating communities of younger MSMSW, which may be contributing to high rates of HIV incidence across Asia in populations of very young MSM. 26 While it is encouraging to see that MSMSW in their 20s may be receiving HIV testing, perhaps as a result of exposure to MSM-focused HIV prevention and sexual health information online, 24 this study demonstrates the importance of reaching communities of young MSM, who may be involved in sex work, with salient HIV testing messages. We also found that having other STIs was associated with a higher likelihood of being tested for HIV.…”
Section: Discussionmentioning
confidence: 81%
“…However, few studies have comparable results. Researches concerning same-sex behavior focused mainly on age and HIV risk [ 39 – 42 ], while others found that older MSM reported less MSM behaviors [ 32 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a higher perceived seriousness of HIV actually delayed participants’ sexual debut. An earlier age of sexual debut has been associated with engaging in sexual risk behaviours and positive HIV status [ 32 , 33 ]. We have observed the inverse; perhaps a later age of sexual debut may in turn be associated with more conservative sexual behaviors or fewer sexual partners, leading to participants’ perception of a lower risk of contracting HIV.…”
Section: Discussionmentioning
confidence: 99%